2008
DOI: 10.12968/ijpn.2008.14.6.30021
|View full text |Cite
|
Sign up to set email alerts
|

What do community palliative care nurse specialists do? An activity analysis

Abstract: A self-assessed activity analysis of a team of community palliative care nurse specialists was undertaken as part of a wider review of their service. Although it was not a research project, it proved to be a pragmatic and worthwhile means of analysing the work of individual nurse specialists and measuring what they actually do. The results and outcomes are presented in order to share the experience and to break down some of the isolation of community palliative nursing practice. The study found quite wide vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This activity aims to provide information to caregivers, shed light on incorrect information about care or delegate some degree of care. 23 , 41 , 47 , 57 , 59 , 62 , 67 , 69 , 73 , 79 , 85 , 90 The nurse may teach basic care practices, key monitoring activities or techniques for administering medication. Teaching to caregivers is frequently described as an activity that empowers the individuals to act towards their goals or intended future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity aims to provide information to caregivers, shed light on incorrect information about care or delegate some degree of care. 23 , 41 , 47 , 57 , 59 , 62 , 67 , 69 , 73 , 79 , 85 , 90 The nurse may teach basic care practices, key monitoring activities or techniques for administering medication. Teaching to caregivers is frequently described as an activity that empowers the individuals to act towards their goals or intended future.…”
Section: Resultsmentioning
confidence: 99%
“…For the patient, the activities identified are mainly generic without going into detail about their nature. 42 , 47 , 52 , 55 , 60 , 68 , 72 , 74 , 79 , 82 , 89 , 90 However, some nursing activities for emotional support are specifically identified, including focused conversations and active listening. 48 , 52 , 54 , 64 , 65 , 67 , 69 , 72 , 75 , 76 , 78 , 80 , 81 , 83 , 84 , 88 , 89 This emotional support activity makes it possible to clarify the patient’s thoughts and goals, particularly with regard to the advance care planning, preferred place of death, preparation of the inheritance and bequests, the desired involvement of caregivers and the resources available.…”
Section: Resultsmentioning
confidence: 99%
“…Although the number of telephone calls was included as an extra variable (for both tools), the duration of calls could not be recorded and this was considered an important omission by participants. Newbury et al (2008) examined a range of activities within clinical contact time and found that, on average, 6.2% and 6.4% of the work schedule of CNSs was spent respectively on telephone calls with other professionals and on telephone calls with patients and their families. This is an important finding as the time spent on phone calls is often overlooked in other studies of nursing care.…”
Section: Discussionmentioning
confidence: 99%